2011
DOI: 10.1177/1059840511426147
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Interventions for Overweight and Obesity in Minority School Children

Abstract: The prevalence of childhood overweight and obesity in the United States has resulted in a number of school-based health interventions. This article provides a review of research that addressed childhood overweight and obesity in minority, U.S. elementary schools. All studies reported some benefits in health behaviors and/or anthropometric measures. Effectiveness was greater when program objectives were specific, implemented across the school environments, extended into the community, and were culturally releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…For school wellness policies to be effective, Johnson (2012) suggests that all parts of the school wellness policy should be implemented. Moreover, investigators also believe that the policy implementation must have sufficient intensity and duration (Jiang et al, 2007; Mauriello et al, 2006; Sharma, 2006; Zahner et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For school wellness policies to be effective, Johnson (2012) suggests that all parts of the school wellness policy should be implemented. Moreover, investigators also believe that the policy implementation must have sufficient intensity and duration (Jiang et al, 2007; Mauriello et al, 2006; Sharma, 2006; Zahner et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In step 2, two reviewers (AT & NM) screened the abstracts of the remaining 305 articles and further excluded articles based on study design (cross-sectional, baseline descriptions), no outcomes reported, a focus on the treatment of obesity and associated chronic conditions, and involving other US-based target populations. In addition, school-based interventions were excluded given recent publications in this area [ 30 32 , 34 ]. In the last step, the full-text versions of the remaining 41 articles were retrieved and screened for inclusion (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Long‐term healthy habits may be established in childhood, which makes this age group within the school setting optimal for COP. School‐based interventions with both minority and nonminority children have used various combinations of COP interventions focusing on nutrition, physical activity, school food services, healthy lifestyle education, parental involvement, and policies, and yielded mixed successes (Johnson, Weed, & Touger‐Decker, ; Shaya, Flores, Gbarayor, & Wang, ; Zenzen & Kridli, ). Many interventions resulted in decreased sedentary activity, reduced dietary fat intake, or increased nutrition knowledge, without significant changes in body mass index (BMI) or differences in overweight and obesity rates (Caballero et al., ; Neumark‐Sztainer et al., ; Warren, Henry, Lightowler, Bradshaw, & Perwaiz, ).…”
Section: Introductionmentioning
confidence: 99%